Dexpramipexole Attenuates White Matter Injury to Facilitate Locomotion and Motor Coordination Recovery via Reducing Ferroptosis after Intracerebral Hemorrhage. (4th August 2022) - Wang, Bo; Zhang, Xuyang; Zhong, Jun; Wang, Shi; Zhang, Chao; Li, Mingxi; Hu, Quan; Wang, Shuhong; Chen, Lin; Chen, Weixiang; Ge, Hongfei; Feng, Hua
Abstract : Deciphering the factors causing damage to white matter fiber bundles and exploring new strategies to alleviate white matter injury (WMI) is a promising treatment to improve neurological impairments after intracerebral hemorrhage (ICH). Ferroptosis usually occurs at perihematomal region and contributes to neuronal death due to reactive oxygen species (ROS) production. Dexpramipexole (DPX) easily crosses the blood brain barrier (BBB) and exerts antioxidative properties by reducing ROS production, while the role of DPX in ferroptosis after ICH remains elusive. Here, our results indicated that ferroptosis played a significant role in WMI resulting from iron and ROS accumulation around hematoma. Further evidence demonstrated that the administration of DPX decreased iron and ROS deposition to inhibit ferroptosis at perihematomal site. With the inhibition of ferroptosis, WMI was alleviated at perihematomal site, thereafter promoting locomotion and motor coordination recovery in mice after ICH. Subsequently, the results showcased that the expression of glutathione peroxidase 4 (GPX4) and ferroptosis suppressing protein 1 (FSP1) was upregulated with the administration of DPX. Collectively, the present study uncovers the underlying mechanism and elucidates the therapeutic effect of DPX on ICH, and even in other central nervous system (CNS) diseases with the presence of ferroptosis.